2007
DOI: 10.1007/s10661-007-9953-2
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of municipal effluent with drip irrigation and evaluation the effect on soil properties in a semi-arid area

Abstract: Irrigation with municipal effluent was evaluated during 25 months in Southern Iran from 2003 to 2005 in which 14 tree species were irrigated with effluent and borehole water at an annual supply rate of 3,940 and 5,395 m(3) ha(-1), respectively. To mitigate the environmental effects, a drip irrigation system was designed and the amount of applied water based on pan evaporation was measured by flow meters and soil properties were monitored. The statistical results showed that the applied effluent had no adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 8 publications
3
13
0
Order By: Relevance
“…In this study, there were no significant changes in soil EC at the lower soil depths of 15-30, 30-45 and 45-60 cm, and no interactive effect of water quality × irrigation scenario on soil salinity was observed. Similar views have been expressed by many investigators who found increases in soil salinity and sodicity in the top soil layer when irrigating with RW (Hassanli et al, 2008;Amiri et al, 2008;Laurenson et al, 2012). Also, other studies involving irrigation with desalinated seawater and RW reported increased soil salinity and sodicity, which were found to be generally higher in DI than in FI treatments (Díaz et al, 2013;Aragüés et al, 2014a).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In this study, there were no significant changes in soil EC at the lower soil depths of 15-30, 30-45 and 45-60 cm, and no interactive effect of water quality × irrigation scenario on soil salinity was observed. Similar views have been expressed by many investigators who found increases in soil salinity and sodicity in the top soil layer when irrigating with RW (Hassanli et al, 2008;Amiri et al, 2008;Laurenson et al, 2012). Also, other studies involving irrigation with desalinated seawater and RW reported increased soil salinity and sodicity, which were found to be generally higher in DI than in FI treatments (Díaz et al, 2013;Aragüés et al, 2014a).…”
Section: Discussionsupporting
confidence: 75%
“…Also, other studies involving irrigation with desalinated seawater and RW reported increased soil salinity and sodicity, which were found to be generally higher in DI than in FI treatments (Díaz et al, 2013;Aragüés et al, 2014a). As mentioned earlier, the high sodium content in RW influenced the SAR, which could lead to reductions in soil permeability and subsequent restrictions of water flow within the soil profile (Hassanli et al, 2008). Mounzer et al (2013) found that use of RW increased the SAR significantly in the upper soil layers.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…As seen in a previous research project [16] the behavior of NH 4 + -N was outwardly odd, depending greatly on both the type and amount of ZT present in the samples. More specifically: (i) mean [NH 4 + ] in SSs was greater than DMW and, on average, greater in OT than in CV suspensions; (ii) mean [NH 4 + ] in ZT suspensions was greater than the respective DMWs and, on average, greater in ZCL than in NYT suspensions; and (iii) SSs/ZT samples showed trends ranging from SSs alone to ZTs alone, approaching the latter as ZT content in SSs/ZTs increased. This behavior can be explained by considering that NH 4 + is preferentially absorbed and strongly retained in samples containing the investigated zeolitized tuffs.…”
Section: Supernatants From Dmw/sample Suspensionsmentioning
confidence: 99%
“…In recent years, the use of both wastewater (WW) and treated WW in agriculture has grown considerably [1] and, as would be expected, a large number of investigations have been carried out worldwide in arid and semi-arid regions considering the advantages and disadvantages of WW application to soil irrigation/fertilization [2][3][4][5][6][7]. One of the main critical points is that WW can pose potential risks to human health and the environment [8][9][10].…”
Section: Introductionmentioning
confidence: 99%